Multidisciplinary interaction and MCD gene discovery. The perspective of the clinical geneticist. (November 2021) - Mancini, Grazia M.S.; Smits, Daphne J.; Dekker, Jordy; Schot, Rachel; de Wit, Marie Claire Y.; Lequin, Maarten H.; Dremmen, Marjolein; Brooks, Alice S.; van Ham, Tjakko; Verheijen, Frans W.; Fornerod, Maarten; Dobyns, William B.; et al.
Abstract: The increasing pace of gene discovery in the last decade has brought a major change in the way the genetic causes of brain malformations are being diagnosed. Unbiased genomic screening has gained the first place in the diagnostic protocol of a child with congenital (brain) anomalies and the detected variants are matched with the phenotypic presentation afterwards. This process is defined as "reverse phenotyping". Screening of DNA, through copy number variant analysis of microarrays and analysis of exome data on different platforms, obtained from the index patient and both parents has become a routine approach in many centers worldwide. Clinicians are used to multidisciplinary team interaction in patient care and disease management and this explains why the majority of research that has led to the discovery of new genetic disorders nowadays proceeds from clinical observations to genomic analysis and to data exchange facilitated by open access sharing databases. However, the relevance of multidisciplinary team interaction has not been object of systematic research in the field of brain malformations. This review will illustrate some examples of how diagnostically driven questions through multidisciplinary interaction, among clinical and preclinical disciplines, can be successful in the discovery of new genes related to brain malformations. The first example illustrates the setting of interaction among neurologists, geneticists and neuro-radiologists. The second illustrates the importance of interaction among clinical dysmorphologists for pattern recognition of syndromes with multiple congenital anomalies. The third example shows how fruitful it can be to step out of the "clinical comfort zone", and interact with basic scientists in applying emerging technologies to solve the diagnostic puzzles. Highlights: The paper reflects the opinion of the authors on the approach to the genetic research in the field of brain malformations. Expertise from different fields, state-of -the-art technologies and interdisciplinary interaction foster advances. Coordinated interdisciplinary approach promises to accelerate discoveries and to improve disease management.